Public values for energy futures: Framing, indeterminacy and policy making. (December 2015) - Butler, C.; Demski, C.; Parkhill, K.; Pidgeon, N.; Spence, A.
Abstract: In the UK there are strong policy imperatives to transition toward low carbon energy systems but how and in what ways such transitional processes might be realised remains highly uncertain. One key area of uncertainty pertains to public attitudes and acceptability. Though there is wide-ranging research relevant to public acceptability, very little work has unpacked the multiple questions concerning how policy-makers can grapple with and mitigate related uncertainties in efforts to enact energy systems change. In this paper, public acceptability is identified as an indeterminate form of uncertainty that presents particular challenges for policy making. We build on our existing research into public values for energy system change to explore how the outcomes of the project can be applied in thinking through the uncertainties associated with public acceptability. Notably, we illustrate how the public values identified through our research bring into view alternative and quite different problem and solution framings to those currently evident within UK policy. We argue that engagement with a wide range of different framings can offer a basis for better understanding and anticipating public responses to energy system change, ultimately aiding in managing the complex set of uncertainties associated with public acceptability. Highlights: We argue that public acceptability represents an indeterminate form of uncertainty. This means alternative approaches to decision-making are required. We introduce a public value set for energy system change. We use this as a basis for interrogating current UK policy approaches to transitions. Incorporating public values in policy can help tackle uncertainty about acceptability.